PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PERUSAHAAN PENGAKUISISI - Khoiriyah Dewi Saputri; Hendrato Setiabudi Nugroho (Cross-border, 2022)
The purpose of this study is to explore the differences in financial performance before and after the acquisition viewed from financial ratios, namely Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), and Total Assets Turn Over (TATO) in acquiring companies listed on the Indonesia Stock Exchange in 2015-2019. An acquisition is a take-over of part or all of the shares of another company so that the acquiring company has control rights over the target company. The data used in this study was secondary data obtained from the annual financial statements of companies that made acquisitions and were listed on the Indonesia Stock Exchange in 2015-2019. The population in this study were all companies listed on the Indonesia Stock Exchange. The sampling method used in this study was purposive sampling. There were 7 companies that entered the criteria of this study. The data were analyzed through descriptive statistics, normality test, and Wilcoxon signed ranks test. The results of the Wilcoxon signed ranks test show that there is a significant difference in the CR financial ratio for testing two years before and after the acquisition of the acquiring company. Meanwhile, there is no significant difference for the financial ratios of TATO, DER, ROA, ROE, and NPM for the two- year test before and after the acquisition of the acquiring company.